A survey on the brand-loyalty among sports products consumers / Suriati Mohd Subri - Mohd Subri, Suriati (2002)
The purpose of this research is to determine and identify cognitive, attitudinal behavioral phenomenon and macro environment forces that influenced and affect the brand-loyal consumers. To achieve these objectives, researcher used questionnaires distribution to 200 random sample respondents at cluster sampling primary units (Bangsar, Subang Jaya, Shah Alam and Klang). The researcher used frequency distribution and cross-tabulation for analyzing the data. As the result of this research, respondents' age between 23-27 year-old, which have monthly income between RM501-RM1000, spent between RM101-RM150 for each purchased and they had chosen Adidas and Nike as their preferred brands. They choose those brands because of quality of the brand name, brand image, satisfaction after buying process, accessibility, market share, advertisement, sates price and availability of the brand in other sport articles. Although, they are loyal, they may change to alternative brands if these situations occurs; desire to try new brand, discount sales, promotion and sates campaign were very attractive.